The burden, predictors and outcomes of acute kidney injury in children admitted to the paediatric intensive care unit at the University Teaching Hospitals’- Children’s Hospital in Lusaka, Zambia - Chambah, Ilunga; Zgambo, Jessy; Wa-Somwe, Somwe; Mwaba , Chisambo (African Journal of Nephrology, 2024)
Background: Acute kidney injury (AKI) is common in critically ill patients and generates poor outcomes as a consequence. There is scant evidence on AKI encountered in paediatric intensive care units (PICU) in low-income countries such as Zambia. We have conducted a prospective study to investigate the burden, predictors, and consequences of AKI in children admitted to a tertiary hospital PICU in Lusaka. Methods: A total of 134 participants, aged 29 days to 18 years and meeting the eligibility criteria, were investigated. Diagnosis of AKI was based on the Kidney Disease Improving Global Outcome (KDIGO) 2012 criteria. A predesigned form was used to collect baseline demographic and clinical data as well as patient outcomes. Data were stored and analysed using SPSS version 25. Results: The median age of the study population was 3.75 years (IQR 5,12), in whom AKI was present in 34%. Children under the age of one year had the highest prevalence of AKI (42%; P = 0.001) and sepsis was the cause in 31% of all AKI patients. Hypernatremia (AOR = 1.115; CI = 1.050–1.185; P = <0.001) and fluid overload (AOR = 6.207; CI = 1.020–37.591; P = <0.047) were predictors of AKI, which was associated with the need for vasopressor support (AOR = 10.015; CI = 1.038–51.763; P = <0.006) and 49% mortality (OR = 2.47; P = <0.008). Children with hospital-acquired AKI (HA-AKI) stayed longer in the hospital (43%) than those with community-acquired AKI (CA-AKI; 2.65% P = 0.001), and required prolonged ventilator support. Conclusion: In this setting, AKI affects a third of PICU patients with infants, sepsis, fluid overload and hypernatremia being associated with a higher risk of developing AKI. This condition was linked to increased need for vasopressors and a high mortality.